A Reanalysis of the 1916, 1918, 1927, 1928, and 1935 Tropical Cyclones of the North Atlantic Basin - Glenn, David Allen (Scholars Junction, 2005)
This thesis research involves a reanalysis of the National Hurricane Center?s Atlantic Basin Hurricane Database (HURDAT) for 1916, 1918, 1927, 1928, and 1935. Newly available meteorological records from ship logs (COADS) along with recently discovered historical documents were used to reassess tropical cyclone location and intensity. Tropical cyclone track and intensity alterations are discussed in detail in a supporting metadata file. The overall results of the reanalysis process were minor alterations, with some major changes, to the track and intensity of tropical cyclones in HURDAT. Four tropical storms were added: one in 1918, one in 1927, and two in 1935. Three tropical storms were deleted: one in 1918 and two in 1916. However, the overall tropical activity remained nearly the same for the study period. This research is significant because it will strengthen our understanding of hurricane climatology and improve forecast models that utilize HURDAT.